Development of a Model to Determine the Purchase Intention of Counterfeit Luxury Products Among Consumers in Bengaluru - Nikita, Annette; Devakumar, G. (Indian Journal of Marketing, 2022)
The luxury fashion industry is a profitable one and is expected to grow at a rate of 10.99% annually. With the luxury industry growing, the counterfeiting industry is also seeing rapid growth. India’s trade has increased by 24% in the last two years. The research attempted to investigate the factors affecting consumers’ attitudes toward the purchase intention of counterfeit luxury products in South-East Bengaluru. The primary data were collected through an online survey questionnaire. Using the cluster sampling technique, a total of 309 responses were received, of which seven were rejected due to incomplete responses. Therefore, a sample size of 302 was seen fit to use for statistical purposes. Based on the identified factors, initially, a conceptual framework was developed, and the model was tested using JMP Pro 16 software. The research findings revealed that low -income group consumers tended to buy counterfeits more often. The ordinal position of birth played a significant role where first-born children showcased an unfavorable attitude. However, later-born children showcased a more positive attitude. Young adults showed an approved attitude toward counterfeits. The social class of students and employees showed an encouraging attitude toward counterfeits. Several personal and social factors were found to have a strong influence on the attitude toward counterfeits. From the findings, suggestions and recommendations have been drawn to assist genuine brands to frame better tactics to curb counterfeiting.